2013
DOI: 10.5271/sjweh.3396
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trials are needed to close the evidence gap in the prevention of preterm birth

Abstract: Randomized controlled trials are needed to close the evidence gap in the prevention of preterm birth by Kwegyir-Afful E, Ijaz S, Räsänen K, Verbeek J Pregnant women have been advised to avoid heavy lifting during pregnancy due to concerns of adverse pregnancy outcomes including premature delivery. To date there is no evidence on the effectiveness of advice in preventing preterm birth as found in a recent systematic search and appraisal of published literature. This letter employs the findings of the review to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Strenuous physical activity, low birthweight and preterm birth are common occurrences in low-income countries without guidelines to protect against hazardous work exposures [11]. There are inconsistencies in the existing etiological studies on the subject thereby creating an evidence gap [22]. As a result of the inconsistencies, recommendations and all other clinical guidelines lack the necessary evidential backing for practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strenuous physical activity, low birthweight and preterm birth are common occurrences in low-income countries without guidelines to protect against hazardous work exposures [11]. There are inconsistencies in the existing etiological studies on the subject thereby creating an evidence gap [22]. As a result of the inconsistencies, recommendations and all other clinical guidelines lack the necessary evidential backing for practice.…”
Section: Discussionmentioning
confidence: 99%
“…In their quest to lengthen gestational age, midwives in LMICs such as Ghana, advise pregnant women against strenuous physical activity. In certain conditions, the pregnant woman is admitted to a hospital throughout the gestational period to ensure complete bed rest to avert possible preterm birth [22]. Besides, there are several occupational guidelines formulated by various institutions [19,23] aimed at protecting pregnant employees against physical stress in their respective countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their quest to lengthen gestational age, midwives in LMIC such as Ghana advise pregnant women against strenuous physical activity. In certain conditions, the pregnant woman is admitted to a hospital throughout the gestational period to ensure complete bed rest to avert possible PTB [ 22 ]. Several occupational guidelines have been formulated by various institutions [ 19 , 23 ] aimed at protecting pregnant employees against physical stress in their respective countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, no such guidelines exist in Ghana and other LMIC. A recent systematic review revealed that no trial has investigated the usefulness of such guidelines aimed at reducing heavy lifting among pregnant women to increase gestational age [ 22 ]. The 3-component liftless intervention implemented in this trial is based on the clinical guidelines of occupational lifting in pregnancy by MacDonald et al [ 24 ] coupled with a shopping voucher.…”
Section: Introductionmentioning
confidence: 99%